2016
DOI: 10.1111/jfpp.13006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Some Essential Oils on the Growth ofPenicillium verrucosumand its Ochratoxin a Production

Abstract: Antifungal activities of four essential oils from mint, garlic, sage and wild oregano were evaluated against ochratoxigenic Penicillium verrucosum incubated at different times. The fungal mycelium growth was completely inhibited (fungicidal effect) at concentrations of 0.5 and 0.25% of the garlic and wild oregano essential oils. However, concentrations of 0.125 and 0.065% of essential oils were showed the low reductions to be 37.05–46.59 and 35.68–45.51%, respectively. Sage essential oil showed the lowest anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Essential oils have been shown to control other species of Penicillium, mainly in foodborne isolates [45][46][47][48]. In agreement with our results, oregano and thyme essential oils have also inhibited the growth of Penicillium verrucosum and Penicillium digitatum, respectively [45,46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Essential oils have been shown to control other species of Penicillium, mainly in foodborne isolates [45][46][47][48]. In agreement with our results, oregano and thyme essential oils have also inhibited the growth of Penicillium verrucosum and Penicillium digitatum, respectively [45,46].…”
Section: Discussionsupporting
confidence: 90%
“…Essential oils have been shown to control other species of Penicillium, mainly in foodborne isolates [45][46][47][48]. In agreement with our results, oregano and thyme essential oils have also inhibited the growth of Penicillium verrucosum and Penicillium digitatum, respectively [45,46]. However, in contrast to our results, clove essential oil has inhibited the P. digitatum and Penicillium expansum growth, and rosemary essential oil has inhibited the P. expansum growth [45,47].…”
Section: Discussionsupporting
confidence: 87%
“…Finally, studies revealed that different essential oils, such as cinnamon, clove, garlic, oregano, sage, and thyme, reduced OTA production by Penicillium verrucosum , and cinnamon, clove, and thyme reduced OTA production by Aspergillus westerdijkiae (Aldred et al., 2008; Ozcakmak et al., 2016).…”
Section: Essential Oilsmentioning
confidence: 99%
“…The inhibitory effects of some essential oils have been widely reported. Melissa officinalis, Salvia officinalis, Coriandrum sativum, Thymus vulgaris, Mentha piperita and Cinnamomum zeylanicum (Sumalan et al 2013), lemon, grapefruit and Cymbopogon martinii (Perczak et al 2016), garlic and Origanum vulgare (Ozcakmak et al 2017) were reported as effective in either inhibiting or reducing the associated mycotoxins activities.…”
Section: Reducing Mycotoxins In the Food Chainmentioning
confidence: 99%